Ter wille van 'n stabiele familie: die literêre konteks van Levitikus 18:22 en 20:13 - M. D. Terblanche (Acta Theologica)
Leviticus 18:22 and 20:13 are the only texts in the Old Testament that explicitly condemn homosexual acts. It is of the outmost importance to take the literary context of these texts into consideration. Both prohibitions have family laws as immediate context. Since homosexual acts drastically influence the relations in the larger family, the prohibitions of these acts were associated with the family laws. Leviticus 18 and 20 are closely connected to Leviticus 19, a chapter that emphasises the holiness of the people. The call to holiness in 19:2 concerns all facets of life including sexual relations. The prohibitions against homosexual acts finally belong to the legislation that was given by Yahweh to Moses at Sinai. Therefore Israel had to take them seriously.